Evaluasi Perbandingan Ranking antara Proposed Value dan Perceived Value terhadap E-ticketing berdasarkan Model UXHoneycomb - Frita Dwi Julianinda; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Traveloka, Tiket.com and Pegipegi are applications as service providers that accommodate the distribution and sale of transportation tickets online. The number of users of a product or application, certainly does not guarantee user experience satisfaction from an application. At present the three e-ticketing applications are able to offer proposed values ​​that can be felt by users when running or using an application. Proposed value is used to provide experience and meet user needs in using the application. This can be utilized in the development of an online based application, namely Traveloka, Tiket.com, and Pegi - Pegi. The application has the value offered to users and the perceived value of user experience. This study aims to evaluate the value that has been given and felt by users using the UX Honeycomb method that can explain the quality of user experience. In UX Honeycomb there are seven aspects namely useful, usable, desirable, findable, accessible, credible, and valueable. The UX Honeycomb aspect will be ranked to get the comparison evaluation results from the proposed value and perceived value in each application. Based on the comparison of the proposed values ​​and the perceived value of each application that needs to be improved on Traveloka is desirable, for Tiket.com, which needs to be improved is findable, while the activities that need to be improved are valueable.